Effects of anthocyanin supplementation on blood lipid levels: a systematic review and meta-analysis - Jang, Hwan-Hee; Hwang, In-Guk; Lee, Young-Min (Frontiers in Nutrition, 2023)
Introduction: Dyslipidemia is a major cardiovascular disease risk factor associated with increased mortality. Intake of plant food-derived bioactive compounds is associated with beneficial cardiovascular effects, including decreased blood lipid levels and cardiovascular risk. We aimed to evaluate the effects of anthocyanin intake on blood lipid levels by analyzing relevant randomized controlled trials. Methods: We searched the PubMed and Embase databases using the "Patient/Population, Intervention, Comparison and Outcomes" format to determine whether anthocyanin-rich food supplementation intervention affected blood lipid levels compared with placebo supplementation in human participants. Results: A total of 41 studies with 2,788 participants were included in the meta-analysis. Anthocyanin supplementation significantly reduced triglyceride (standardized mean difference [SMD] = -0.10; 95% confidence interval [CI], -0.18, -0.01) and low-density lipoprotein-cholesterol (SMD = -0.16; 95% CI -0.26, -0.07) levels and increased high-density lipoprotein-cholesterol levels (SMD = 0.42; 95% CI 0.20, 0.65). Discussion: Anthocyanin supplementation significantly improved all blood lipid component levels in the included studies. Larger, well-designed clinical trials are needed to further investigate the effects of anthocyanin intake on blood lipid levels and the safety of anthocyanin-rich food supplementation for treating dyslipidemia.